2022
DOI: 10.3389/fmicb.2022.916089
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-induced intestinal dysbiosis is associated with the exacerbation of Sjogren’s syndrome

Abstract: Environmental factors are believed to influence the evolution of primary Sjögren’s syndrome (pSS). The aims of this study were to investigate the association of pSS with a high-fat diet (HFD) and to relate HFD-induced gut dysbiosis to pSS exacerbation. Male Wild Type (WT) and IL-14α transgenic mice (IL-14α TG) were fed a standard diet (SD) and HFD for 11 months. We found an increase in the autoantibody level, more severe dry eye, severe dry mouth symptoms, and an earlier presence of systemic features in the IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Indeed, there is evidence that the colonization of germ-free mice with the GM derived from Sjögren's syndrome patients decreases the abundance of CD4 + forkhead box P3 (FOXP3) + Treg cells in cervical lymph nodes and promotes corneal barrier damage following dry eye induction [141]. Moreover, feeding IL-14α transgenic mice (overexpressing human IL-14α; a model of Sjögren's syndrome) with a high-fat diet correlates with reduced GM richness, overgrowth of intestinal Deferribacterota, and worse dry eye manifestations [142]. Still, in another mice study in which dry eye pathology was induced by desiccation stress (applied to the ocular surface using a ventilator) with or without scopolamine (an antimuscarinic agent), the obtained findings show that this type of stress is able to change the GM, with an increase in the Proteobacteria and a decrease in Bacteroides and Firmicutes in comparison with unstressed mice [143].…”
Section: Dry Eye Diseasementioning
confidence: 99%
“…Indeed, there is evidence that the colonization of germ-free mice with the GM derived from Sjögren's syndrome patients decreases the abundance of CD4 + forkhead box P3 (FOXP3) + Treg cells in cervical lymph nodes and promotes corneal barrier damage following dry eye induction [141]. Moreover, feeding IL-14α transgenic mice (overexpressing human IL-14α; a model of Sjögren's syndrome) with a high-fat diet correlates with reduced GM richness, overgrowth of intestinal Deferribacterota, and worse dry eye manifestations [142]. Still, in another mice study in which dry eye pathology was induced by desiccation stress (applied to the ocular surface using a ventilator) with or without scopolamine (an antimuscarinic agent), the obtained findings show that this type of stress is able to change the GM, with an increase in the Proteobacteria and a decrease in Bacteroides and Firmicutes in comparison with unstressed mice [143].…”
Section: Dry Eye Diseasementioning
confidence: 99%
“…Besides contributing to the development of obesity through the first 12 weeks, diet D2 generated significant changes in the GM composition, resulting in an increase in Firmicutes and a decrease in Bacteroidota , which is in agreement with findings reported previously [ 7 , 13 , 14 , 45 , 46 ]. In addition, other differences previously reported, such as increases in Campylobacterota [ 47 ], Cyanobacteria [ 48 ], Deferribacterota , and Desulfobacterota [ 49 , 50 ], were evidenced. These taxa are considered harmful or potentially pathogenic, as they favor the development of inflammation and alter the intestinal microenvironment, generating changes in intestinal permeability, enabling, in turn, the development of metabolic endotoxemia [ 49 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 66%
“…Because of the different microbial modulations in each group, the potential regulation pathway for each polyphenol was highlighted by the Mantel test. 42 It was shown that the gut microbiota structures of FP and CON were significantly correlated to the gene and protein expressions of CPT-1, and HFD and UFP were significantly correlated to the gene and protein expressions of GPx1. These results indicated that, at the same dosage treatment, the principal regulation effect of FP might be via the AMPK/PPAR α /CPT-1 pathway, and the AMPK-mediated antioxidant pathway for UFP.…”
Section: Discussionmentioning
confidence: 96%